Sandwich-Type Microporous Carbon Nanosheets for Enhanced Supercapacitor Performance - Hao, Guang-Ping; Lu, An-Hui; Dong, Wei; Jin, Zhen-Yu; Zhang, Xiang-Qian; Zhang, Jin-Tao; Li, Wen-Cui (Advanced energy materials, 2013)
Sandwich‐type microporous hybrid carbon nanosheets (MHCN) consisting of graphene and microporous carbon layers are fabricated using graphene oxides as shape‐directing agent and the in‐situ formed poly(benzoxazine‐co‐resol) as carbon precursor. The reaction and condensation can be readily completed within 45 min. The obtained MHCN has a high density of accessible micropores that reside in the porous carbon with controlled thickness (e.g., 17 nm), a high surface area of 1293 m2 g−1 and a narrow pore size distribution of ca. 0.8 nm. These features allow an easy access, a rapid diffusion and a high loading of charged ions, which outperform the diffusion rate in bulk carbon and are highly efficient for an increased double‐layer capacitance. Meanwhile, the uniform graphene percolating in the interconnected MHCN forms the bulk conductive networks and their electrical conductivity can be up to 120 S m−1 at the graphene percolation threshold of 2.0 wt.%. The best‐practice two‐electrode test demonstrates that the MHCN show a gravimetric capacitance of high up to 103 F g−1 and a good energy density of ca. 22.4 Wh kg−1 at a high current density of 5 A g−1. These advanced properties ensure the MHCN a great promise as an electrode material for supercapacitors. Sandwich‐type carbon nanosheets with abundant accessible micropores are synthesized by using a small amount of graphene oxide as a shape‐directing agent and the in‐situ‐formed poly(benzoxazineco‐resol) as the carbon precursor. Such a unique hybrid structure is favorable to the charge storage and rapid diffusion of electrolyte ions and the graphene layers can facilitate the transport of electrons, which leads to the outstanding supercapacitor performance.